Anisotropy of Ferromagnetic Heusler Alloys Thin Films - Yilgin, R.; Aktas, B. (Springer-Verlag Berlin, 2009)
The Gilbert damping constant was investigated in CO2MnSi Heusler alloy thin films by ferromagnetic resonance (FMR) technique. Samples were prepared using the magnetron sputtering technique on SiO2 substrate for polycrystalline and on a MgO(100) substrate for single crystalline and than annealed at various temperatures to control the structure. The magnetic properties such as g-value, effective magnetization magneto-crystalline anisotropy constant and uniaxial anisotropy constant and intrinsic Gilbert damping constant were obtained from angular dependences of resonance field and peak-to-peak line widths fitting from FMR, spectra using Landau-Lifshitz-Gilbert equation. The minimum-damping constant was obtained for epitaxially growth film annealed at 300 degrees C.
International Conference on Nanoscale Magnetism (ICNM-2007) -- JUN 25-29, 2007 -- Istanbul, TURKEY
Keywords: Gilbert Damping Constant; Spin-Polarized Current; Resonance Linewidth; Magnetic-Properties; Fe Films; Single; Cu; Magnetoresistance; Porosity; Ta